2022
DOI: 10.1111/eva.13448
|View full text |Cite
|
Sign up to set email alerts
|

Isolation‐by‐distance and isolation‐by‐oceanography in Maroon Anemonefish (Amphiprion biaculeatus)

Abstract: Obtaining dispersal estimates for a species is key to understanding local adaptation and population dynamics and to implementing conservation actions. Genetic isolation‐by‐distance (IBD) patterns can be used for estimating dispersal, and these patterns are especially useful for marine species in which few other methods are available. In this study, we genotyped coral reef fish ( Amphiprion biaculeatus ) at 16 microsatellite loci across eight sites across 210 km in the central Philippines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 129 publications
0
3
0
Order By: Relevance
“…For example, most dispersal in the brooding coral Seriatopora hystrix is within 100 m of the natal site, but rare long-distance dispersal of 9 km or more is possible (223). In addition, dispersal distances within species can differ substantially between locations because of variations in ocean currents, with stronger currents driving more widespread gene flow (47,73).…”
Section: Population Genomic Processes On Coral Reefsmentioning
confidence: 99%
“…For example, most dispersal in the brooding coral Seriatopora hystrix is within 100 m of the natal site, but rare long-distance dispersal of 9 km or more is possible (223). In addition, dispersal distances within species can differ substantially between locations because of variations in ocean currents, with stronger currents driving more widespread gene flow (47,73).…”
Section: Population Genomic Processes On Coral Reefsmentioning
confidence: 99%
“…The isolation of offshore populations compared with high coastal connectivity highlights the importance of bathymetric barriers, rather than isolation‐by‐distance, which has been observed in many other elasmobranchs. Fitz et al ( 2022 ) focused on the population genetic patterns of the anemonefish Amphiprion biaculeatus , comparing different geographic determinants of genetic structure. Here, the authors present models detailing whether spatial distance or dispersal with currents best explained genetic separation in this rare reef fish and concluded that, while oceanographic currents best explained genetic patterns at large scale (>150 km), isolation‐by‐distance was a stronger determinant at smaller geographic scales.…”
Section: Overview Of the Issuementioning
confidence: 99%
“…Herein, these processes are addressed in diverse empirical model systems ranging from diatoms to mollusks and fish (Green et al, 2022 ; Le Moan et al, 2022 ; Sefbom et al, 2022 ; Zhang et al, 2022 ), as well as in silico in two theoretical modeling studies (Eriksson et al, 2022 ; Marshall & Connallon, 2022 ). The link between genotype and phenotype is also the focus of several empirical studies here (Gefaell et al, 2022 ; Stenger et al, 2022 ; Walker et al, 2022 ), as is the seascape genomics of a wide range of taxa (Delaval, Bendall, et al, 2022 ; Delaval, Frost, et al, 2022 ; Fitz et al, 2022 ; Lapègue et al, 2022 ; Matias et al, 2022 ; Palumbi et al, 2022 ; Pampoulie et al, 2022 ), which has important implications for management of marine resources. Finally, the breadth of phylogenetic diversity and evolutionary history in the oceans is the topic of several articles focusing on the larval development of gastropods (Korshunova et al, 2022 ; Sun et al, 2022 ) and the evolution of small RNAs in cnidarians (Li & Hui, 2022 ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, cultural production takes precedence over meeting the international market demand for environmental information (Prasetio and Kusrini, 2012). In addition, this fish has a unique reproduction system due to its social hierarchical system, protandrous hermaphroditism, and monogamous system (Madhu et al, 2013;Klann et al, 2021;Fitz et al, 2022). This condition marks the difficulties of mass artificial spawning, limiting the seed stock and broodstock candidate supply in culture production.…”
Section: Introductionmentioning
confidence: 99%